KEANEKARAGAMAN JENIS TUMBUHAN DI HUTAN MANGROVE KECAMATAN TOMBARIRI KABUPATEN MINAHASA - Ziman F. Dekme; Marthen T. Lasut; Alfonsius Thomas; Reynold P. Kainde (COCOS, 2016)
ABSTRACT This research took place at four villages (Poopoh, Teling, Kumu, and Pinasungkulan) in the District of Tombariri from May to June 2015.  It was aimed to determine the diversity of mangrove forest trees using explorative method for species identification as well as their morphology structure.  Vegetative features include roots, bark, leaf, flower, fruit, and colour. In addition to that, community use of the mangrove was also studied.  Results show that 8 species were found and belonged to 5 families (Avicenniaceae, Rhizophoraceae, Arecaceae, Sonneratiaceae, and Pandanaceae).  From Rhizophoraceae there are 3 species (Bruguiera clyndrica, Rhizophora stylosa, Rhizophora apiculate); from Sonneratiaceae there are 2 species (Sonneratia alba and Sonneratia ovata); followed by 1 species each for the rest of the families, that is, Avicennia alba from Avicenniaceae, Nypa fruticans from Arecaceae, and Pandanus sp. from Pandanaceae. Keywords: Tombariri, mangrove, Avicenniaceae, Rhizophoraceae, Arecaceae, Sonneratiaceae, Pandanaceae